SOSIALISASI POKDARWIS DALAM MENDORONG PARTISIPASI MASYARAKAT UNTUK MEWUJUDKAN DESA WISATA DI DESA BINAKAL KABUPATEN BONDOWOSO - Diana Permata Nur Mifdatun Jannah; Zaidan Rizqullah Luqianto; M. Daffa Rakhamsyah Yaafi; Liandra Alifia; Safa Adista Sekar Sakanti; Nabila Uswatun Hasannah; Annisa Zerlina Cindy Gayatri; M. Khatam Ramadhan; M. Erick Lucky Hafifi; Luluk Ulfah; Murtaqib (GANESHA: Jurnal Pengabdian Masyarakat, 2024)
Indonesia is a country that has natural wealth, art and culture with great potential to become a tourism attraction. The development of tourism villages has a great opportunity as the foundation of the regional economy. A village that has the potential to become a tourist village is Binakal Village from Binakal District, Bondowoso Regency, East Java, which has natural beauty, art and culture that has the potential to be introduced to a wide audience. Tourism in the village needs to empower the community by involving community organizations such as the Tourism Awareness Group (Pokdarwis). Binakal Village previously had a Pokdarwis, but it was inactive so it needed to be reactivated by educating the importance of Pokdarwis in supporting the formation of a tourist village. The method of service of KKN students is by conducting Pokdarwis socialization together with the Bondowoso Regency Tourism, Culture, Youth and Sports Office. The result of the socialization was an increased understanding of tourism villages and Pokdarwis and a growing motivation to realize tourism villages. Keywords: Tourisme Villages, Socialization, Pokdarwis